Non-specialist psychosocial support interventions for women living with HIV: A systematic review. Issue 9 (2nd September 2017) - Beres, Laura K.; Narasimhan, Manjulaa; Robinson, Jennifer; Welbourn, Alice; Kennedy, Caitlin E.
ABSTRACT: Many women living with HIV experience a range of physical, social, and psychological challenges linked to their HIV status. Psychosocial support interventions may help women cope with these challenges and may allow women to make better decisions around their sexual and reproductive health (SRH), yet no reviews have summarized the evidence for the impact of such interventions on well-being and SRH decision-making among women living with HIV. We systematically reviewed the evidence for non-specialist delivered psychosocial support interventions for women living with HIV, which are particularly relevant in low-resource settings. Outcomes of interest included mental, emotional, social well-being and/or quality of life, common mental health disorders, and SRH decision-making. Searching was conducted through four electronic databases and secondary reference screening. Systematic methods were used for screening and data abstraction. Nine articles met the inclusion criteria, showing positive or mixed results for well-being and depressive symptoms indicators. No studies reported on SRH decision-making outcomes. The available evidence suggests that psychosocial support interventions may improve self-esteem, coping and social support, and reduce depression, stress, and perceived stigma. However, evidence is mixed. Most studies placed greater emphasis on instrumental health outcomes to prevent HIV transmission than on the intrinsic well-being and SRH of women living with HIV. Many interventions included women living with HIV in their design and implementation. More research is required to understand the most effective interventions, and their effect on sexual and reproductive health and rights.